Alih Fungsi Lahan Sawah di Kecamatan Blahbatuh Kabupaten Gianyar - PUTRA, ANAK AGUNG PUTU NARAYANA YUDI; SUDARMA, I MADE; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Change of Function of Rice Field in Blahbatuh District, Gianyar Regency Land use change is something that is difficult to avoid for both the agricultural and non-agricultural sectors. The reduction of land for irrigated rice farming in Gianyar Regency in the last 5 years reached 386 ha and specifically in Blahbatuh District reached 139 ha. Saba Village as one of the villages in Blahbatuh District has the most decline, which is 35 ha. This reduction in land occurred in the 5-year period from 2013-2017. This study analyzed the rate of conversion of rice fields in Saba Village and the sustainability of the existence of rice fields in Blahbatuh District. The study uses purposive sampling with a total of 30 respondents. The research method used in this study is Multidimensional Scaling (MDS). The results show that during the last five years the average rate of decline in the rice field area has reached 2% per year. The sustainability status of the three dimensions shows that the economic and environmental dimensions are very sustainable, while the social dimension is quite sustainable so that intervention in the social dimension is needed. Based on the results of the research, it is hoped that the Government, especially the Gianyar Regency Agriculture Office, provides more support for farmers by providing incentives to farmers who keep their rice fields and continue to farm and provide assistance to farmers who experience problems in their agricultural production processes.